Diagnosis and Surgical Repair for Coarctation of the Aorta With Intracardiac Defects: A Single Center Experience Based on 93 Infants - Wu, Yuhao; Li, Jiashan; Wu, Chun; Zhu, Jin; He, Ling; Feng, Chuan; Yang, Yiting; Jin, Xin (Frontiers in Pediatrics, 2020)
Introduction: This study aims to summarize the clinical characteristics of coarctation of the aorta (CoA) associated with intracardiac anomalies in infants. Methods: Medical records of 93 infants who were diagnosed with CoA and intracardiac anomalies from August 2009 to August 2018 were retrospectively reviewed. Results: All of the 93 infants underwent single-stage repair for CoA associated with intracardiac anomalies. The mean operative time was 264.6 ± 57.1 min, and the time of ICU stay was 7.0 ± 4.1 days. The residual transcoarctation pressure gradient before discharge was lower than the pressure gradient prior to surgery (48.3 ± 17.5 vs. 22.4 ± 9.6 mmHg, P < 0.01). Early death before discharge was found in five infants. The mean follow-up time of 88 hospital survivors was 40.0 ± 26.4 months, and no subsequent death occurred in the follow-up. Transcoarctation pressure gradient of the 88 survivors in their last follow-up was 19.6 ± 10.5 mmHg. The pressure gradient of 27 cases was higher than 20 mmHg. Significant lower limb retardation was observed in four cases; therefore, balloon angioplasty consult was recommended. The cumulative recoarctation-free survival rate in 3-year follow-up was 73.5%. Conclusions: To avoid secondary operations in early period, single-stage repair of CoA associated with intracardiac anomalies was effective and safe, and the outcomes in early to mid-term follow-up were satisfactory.